Paired words in the poetic genres of Russian children's folklore - Tamara N. Erina; Eduard V. Fomin (Этническая культура, 2025)
The work is devoted to the study of a particular problem of children's speech - paired words that exist in folklore texts - counting rhymes, roll-call-teasers, chants. The sources of factual material were collections with samples of children's oral folklore. The lexemes considered in the article were extracted by the method of continuous sampling. The study is based on the descriptive method, which is important for determining the functional features of paired words in the named genres. Unlike the Turkic and Finno-Ugric languages, where paired words are perceived as ordinary vocabulary and their problems are developed quite well, in Russian linguistics they have become the object of close study only recently. The article reveals the functions of paired words, conditioned by the specifics of the child’ perception, and determines their role in the formation of the linguistic consciousness of children. Paired words in poetic genres of Russian children's folklore perform a rhythmic-melodic function: they create a clear rhythm that organizes the text, make it convenient for memorization, pronunciation or singing, develop the child's linguistic intuition, sound repetitions and alliterations contribute to the development of phonetic hearing. Along with this, the study of paired words in children's folklore allows a deeper understanding of the mechanisms of transmission of linguistic traditions, contributes to the preservation of cultural memory.